Analysis of factors affecting market performance with financial performance as an intervening variable - Mulyati, Sri; Ismawati, Ismawati; Umiyati, Indah (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine the effect of diversification of business, working capital efficiency, and income variability on market performance with financial performance as intervening variables. The population used in this study is a company listed in IDX Quality 30 on the Indonesia Stock Exchange in 2020-2021 with purposive sampling as a method in sample selection and obtained sample of 36 companies. The data obtained is processed using regression analysis, path analysis, t test and F test. The results of this study showed the coefficient of determination was 38,6% and the remaining 61,4% was explained by other variables. Simultaneously diversified business, working capital efficiency, income variability and financial performance affect the market performance. Partially diversified and income variables do not affect the market performance, working capital efficiency has negative effects on market performance while financial performance has a positive effect on market performance. Meanwhile, financial performance is only able to mediate the relationship between working capital efficiency on market performance and unable to mediate the relationship of diversification of business and income variability on market performance.